Hubungan Program Prioritas Desa dengan Struktur Ekonomi Lokal: Studi Tingkat Desa di Maluku Utara - Mohamad Yusuf; Anissa Amoretta Hidayah (Direktorat Sistem Perbendaharaan, 2023)
This study aims to identify Village Fund activities that influence village economic development in North Maluku Province and examine the impact of village priority program policies on village economic structure in the North Maluku region. The method used is tagging and panel data regression with a fixed effect model. The results of the study show that (1) Village Fund activities in the economic dimension were mostly used to support regional openness, especially during the pre-Covid-19 pandemic period, whereas during the pandemic the priority of their use shifted to economic recovery programs; (2) an increase in Village Funds and the presence of BUMDes reduces the composition of the tertiary sector workforce and increases the composition of the primary and secondary sector workforce. These findings indicate that Village Funds and BUMDes have an impact on changes in the village economic structure in the North Maluku region.